Effects of vegetation in the thermal performance of housing in a tropical environment / Alamah Misni - Misni, Alamah (Research Management Institute (RMI), 2011)
In tropical cities, the exterior environment is extremely warm due to the high temperature especially during dry seasons. Solar heat passing through windows and being absorbed through the walls and roofs is the major reason for air-conditioner use. Air-conditioning is the only way to create and maintain a comfortable interior temperature. It has been found that a majority of household spend more than 36.7% of electricity power for cooling and which increases every year. Strategically placed vegetation around a building has long been recognised as a means of cooling. Vegetation can reduce temperature and humidity through shading, evapotranspiration and wind channelling. The appropriate amount, type and placement of vegetation can save the residential cooling demand on a hot and humid day. However the effect of the immediate surrounding vegetation on the cooling load and costs of single dwellings in tropical environment has not been widely recognized and quantified. Monitoring of household electricity use in the two study areas has shown that night time is when most of the air conditioning energy is used, because most households only spend their time at home at night. The critical building envelope surfaces of the house are in east and west side where the sun moves and creates the highest temperature and heat gain to the building in morning and afternoon, and retains the heat until night time. Proper placement of trees, shrubs, vines, groundcover, and turf can greatly reduce the temperature gain to the building and the energy use. The study will determine the potential for energy saving for a single-family house located in a hot and humid tropical environment, through the strategic planting of vegetation.